BIOSORPTION OF CHROMIUM (VI) IONS USING SUSTAINABLE EGGSHELL IMPREGNATED PANDANUS AMARYLLIFOLIUS ROXB. ADSORBENT - Chan Jia Xin; Norzita Ngadi (PERINTIS eJournal, 2021)
The conventional methods used for heavy metals removal from wastewater are cost inefficient and non-ecofriendly. Thus, biosorption using waste materials was proposed in this study. The study was carried out to remove chromium (VI), Cr (VI) ions using raw eggshell and hybrid eggshell-pandan biosorbent. The result obtained showed that the hybrid sorbent had higher efficiency in removal of Cr (VI) ions. The experimental results had indicated that in order to achieve the optimum Cr (VI) ions removal percentage of 17.78%, the optimum conditions required for the raw eggshell sorbent were 140 minutes of contact time, 0.5 g of sorbent, room temperature, pH 5 and initial concentration of 0.8 mg/L Cr (VI) ions solution. While for hybrid eggshell-pandan sorbent, an optimum removal percentage at 37.88% could be achieved when the contact time is 140 minutes, with 0.5 g dosage, 50°C, pH 4 and initial concentration of 0.8 mg/L Cr (VI) ions solution. The study showed that the adsorption of Cr (VI) ions onto the hybrid sorbent follows the pseudo-second-order kinetic model of Legergren, Freundlich isotherm model and the thermodynamic study showed negative values of Gibb’s energy, positive value of enthalpy (16.68 kJ/mol) and entropy change (0.0473 kJ/mol). In short, the hybrid eggshellpandan sorbent has greater potential as a biosorbent in removing Cr (VI) ions compared to that of raw eggshell sorbent.